واقع التعليم عن بعد في جميع أطوار التعليم في الجزائر - وهيبة, د/ قحام; وسيلة, د/السبتي (Sciences humaines; Vol. 40 (2015): SCIENCES HUMAINES (Juin 2015), 2015)
بفضل الثورة العلمية والتكنولوجية وصل التعليم الى أكبر قدر ممكن من الافراد، فتم ابتكار أساليب ومناهج تعليمية جديدة وحديثة لمواجهة تحديات فرضها الوضع الجديد، الا وهي زيادة الطلب على التعليم ونقص الفرص وعدد المؤسسات التعليمية، كل هذا أدى الى انتشار واتساع المعرفة بظهور أنماط جديدة من التعليم جاءت لسد النقص والعجز الذي يواجهه النظام التقليدي ألا وهو التعليم عن بعد، والذي نجح وانتشر في كل دولوالجزائر حققت تجارب وشراكات ناجحة في هذا المجال. لكلمات المفتاحية: التعليم عن بعد، التعليم المفتوح، التعليم الاكتروني، التعليم في الجزائر.           Thanks to scientific and technological revolutionarrivededucation to the maximum amount of people, and wasdevising new methods and modern educational curricula to meet the challenges imposed by the new situation, namely the increaseddemand for education and the lack of opportunities and a number of educational institutions, all thisled to widespread and breadth of knowledge of the emergence of new patterns of Education It came to meet the shortfallfaced by the traditional system, namely distance education, and whomanaged to spread in all countries of Algeria and the experiences and successfulpartnerships have achieved in this area. Key words: Distance education, open education, education-Mail, Education in Algeria.